Pregnancy cholestasis - Poma, Pedro A. (2013)
Intrahepatic cholestasis of pregnancy (ICP) consists in pruritus that develops in the second half of pregnancy and is not associated with other dermatological or systemic problems. ICP diagnosis is confirmed by increase in maternal serum bilirubin, liver enzymes and fasting biliary acids. ICP is associated with fetal meconium passage, prematurity and fetal death. Treatment with ursodeoxycholic acid (UDCA) improves pruritus, maternal laboratory anomalies and fetal outcomes. ICP has a relative benign maternal course but compared to women without this complication ICP women have increased risk in developing hepatobiliar problems, breast cancer and hypothyroidism. Long-term follow up is recommended. Key words: Pregnancy, pruritus, cholestasis, adverse fetal outcomes.